Optimizing Emotional Intelligence as a Preventive Strategy Against Immune System Dysfunction in the Elderly - Husnan, Husnan; Lestari, Siti Mona Amelia; Marliana, Thika; Yustita, Annisa Tri; Judijanto, Loso (Journal of Health and Nutrition Research, 2025)
Aging is marked by physiological and psychological changes, including diminished immune function that increases susceptibility to infections and chronic diseases. This study explores the role of Emotional Intelligence (EI) in preventing immune system dysfunction among the elderly using a mixed-methods sequential explanatory design. Quantitative data were collected through surveys assessing EI and immune biomarkers (IL-6, CRP, cortisol), while qualitative interviews explored emotional regulation strategies and perceived impacts on immune health. The results revealed a significant inverse correlation between EI levels and inflammatory markers, including IL-6 (r = -0.45, p < 0.01) and CRP (r = -0.38, p < 0.05). Participants with higher EI scores also demonstrated more stable cortisol rhythms and better vaccine response rates (p < 0.05). Results show that higher EI levels in older adults are linked to lower inflammation, greater stress resilience, and improved immune homeostasis. These findings suggest that EI acts not only as a psychological asset but also as a physiological buffer, modulating neuroimmune pathways crucial for systemic health in aging. Qualitative insights highlighted adaptive emotional regulation strategies—such as mindfulness, proactive coping, and emotional reframing—as key contributors to immune resilience. Social connectedness, self-awareness, and stress management emerged as vital components of psychological and physiological well-being. This study advocates for integrating EI-based interventions—such as mindfulness training, emotional coaching, and social-emotional learning—into geriatric care. By adopting a holistic biopsychosocial model, EI can serve as a strategic tool for enhancing immune function and overall well-being among older adults.